2018
DOI: 10.14739/2310-1210.2018.1.121990
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of clinical neuroimaging assessment scales using for patient severity in the onset of cerebral hemorrhagic supratentorial stroke to predict the outcome of the disease acute period

Abstract: The main purpose of the study was to determine the criteria for the vital and functional prognosis of the cerebral hemorrhagic supratentorial stroke (CHSS) acute period outcome based on the Hemphill Intracerebral Hemorrhage (Hemphill-ICH) Scale and ICH-Grading Scale (ICH-GS) in the onset of the disease. Materials and methods. A prospective, cohort, complex clinical and paraclinical study was conducted in 124 patients (72 men and 52 women, mean age 64.7 ± 1.1 years) with CHSS. This study included clinical asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…At the same time, the results of our previous study showed a significantly lower informative value of the oICH Scale when used to evaluate a short-term functional prognosis in this cohort of patients [7]. All of the above justifies the search for alternative tools for clinical neuroimaging scoring.…”
Section: а а кузнєцовmentioning
confidence: 65%
“…At the same time, the results of our previous study showed a significantly lower informative value of the oICH Scale when used to evaluate a short-term functional prognosis in this cohort of patients [7]. All of the above justifies the search for alternative tools for clinical neuroimaging scoring.…”
Section: а а кузнєцовmentioning
confidence: 65%